The Oromo Conception of Life: An Introduction* - Kelbessa, Workineh (2013)
This article examines the Oromo conception of life. The Oromo believe that Waaqa is the creator of all things and the source of all life. Accordingly, the concept of “artificial life” does not exist in the Oromo worldview. Life is a sophisticated system and can only be created by a perfect being. Human beings are not above other creatures and cannot despoil them as they wish. They are part of the natural world that is given a special place in the diversity of the cosmos; they are endowed with the intelligence that enables them to understand cosmic events. Thus, God requires humans to responsibly cohabit the Earth with other creatures. This study relies on literature review, interviews and personal observation.
Keywords: artificial life -- Gadaa -- God -- Oromo -- worldview